Plan de marketing para la comercialización de los servicios de enseñanza automovilística del centro de enseñanza automovilística y motociclismo fórmula 1. (2015)
The Center for Automotive and Motorcycling Education Formula One has 24 years of experience providing services in the Armenia city, during which time it has established itself as one of the leading companies in this sector. However, in recent years there has been a considerable increase in the number of companies offering these types of services, reason that the competition for the market has intensified, even to non-compliance with industry regulations by other companies, in order to easily attract customers. For this reason, the Center for Automotive and Motorcycling Education Formula One has identified the need to develop strategies that allow publicizing the advantages of its services through massive activities promoting them and establishing agreements with companies of the city to attract potential customers that have not been addressed. According to the above, the internship consists of developing a marketing plan for the commercialization of the automobile education services of company mentioned, starting with a diagnosis of the current situation of the company in its commercial aspect, to end with the implementation of the strategies set out in the proposed marketing plan.